System Quality and the Impact of the Use of the Flo Application on Free Association Within the Community in Padang City Using the Delone and Mclean Method - Nailul Hikmi; Fitni Hidayati (CV. Get Press Indonesia, 2025)
This study aims to analyze the quality of the Flo application system and its impact on social interactions and the prevalence of free social relationships in the city of Padang. Utilizing the DeLone and McLean model, the research focuses on three primary dimensions: system quality, information quality, and service quality. The findings suggest that higher quality in these areas significantly influences user satisfaction and engagement with the application. Moreover, the study explores the implications of increased social connectivity facilitated by the Flo application, examining both positive and negative effects on social behavior within the community. By collecting data through surveys and interviews, this research provides insights into the net benefits experienced by users, highlighting the potential for applications like Flo to reshape social norms and interactions. Recommendations for future development of the application are also discussed, emphasizing the need for features that promote positive social engagement while mitigating the risks of excessive free social interaction.